Prevalence of chronic thromboembolic pulmonary hypertension after acute pulmonary embolism - Guérin, Laurent; Couturaud, Francis; Parent, Florence; Revel, Marie-Pierre; Gillaizeau, Florence; Planquette, Benjamin; Pontal, Daniel; Guégan, Marie; Simonneau, Gérald; Meyer, Guy; Sanchez, Olivier (Thrombosis and Haemostasis, 2014)
Chronic thromboembolic pulmonary hypertension (CTEPH) has been estimated to occur in 0.1–0.5% of patients who survive a pulmonary embolism (PE), but more recent prospective studies suggest that its incidence may be much higher. The absence of initial haemodynamic evaluation at the time of PE should explain this discrepancy. We performed a prospective multicentre study including patients with PE in order to assess the prevalence and to describe risk factors of CTEPH. Follow-up every year included an evaluation of dyspnea and echocardiography using a predefined algorithm. In case of suspected CTEPH, the diagnosis was confirmed using right heart catheterisation (RHC). Signs of CTEPH were searched on the multidetector computed tomography (CT) and echocardiography performed at the time of PE. Of the 146 patients analysed, eight patients (5.4%) had suspected CTEPH during a median follow-up of 26 months. CTEPH was confirmed using RHC in seven cases (4.8%; 95%CI, 2.3 – 9.6) and ruled-out in one. Patients with CTEPH were older, had more frequently previous venous thromboembolic events and more proximal PE than those without CTEPH. At the time of PE diagnosis, patients with CTEPH had a higher systolic pulmonary artery pressure and at least two signs of CTEPH on the initial CT. After acute PE, the prevalence of CTEPH appears high. However, initial echocardiography and CT data at the time of the index PE suggest that a majority of patients with CTEPH had previously unknown pulmonary hypertension, indicating that a first clinical presentation of CTEPH may mimic acute PE.
Keywords: Pulmonary embolism; chronic thromboembolic pulmonary hypertension; epidemiology; echocardiography